(untitled) (Journal of the College of Basic Education, 2020)
In this work, the display of Chebyshev Wavelets (CW) functions and their Operational Matrix of Integration (OMI) are provided. The method is based on the approximation of the first Chebyshev wavelets. It has been applied to solve signal processing such as electricity consumption signals in addition to medical applications and some Integro-Differential Equations (IDE). In the end, some of numerical examples and applications of signal processing are given, they are solved by using the presented method and we found that this method is the most efficient way, The signal was processed using the proposed method and denoise from it and the Matlab program was used after processing the proposed theory to be used to solve all the above problems.